تحليل الأخطاء في نطق الحروف الهجائية في مهارة القراءة لدى تلاميذ الصف التاسع في معهد سيماطركيس بباسامان الشرقية - Rika Fitri Handayani (Fakultas Tarbiyah Universitas Ibrahimy, 2022)
The purpose of this study is to determine the analysis of the pronunciation errors of the alphabet in the reading skills of ninth grade students at Sematrix Institute in East Basaman. The type of research used by the researcher in this research is field research. The tools used to collect information are observation, interviews and documentation. As for the results of the study, the pronunciation errors of the alphabet in the reading skills of the novice Symatrix students in East Basaman were twenty letters. Reasons for errors in the pronunciation of the alphabet on the reading skills of beginner Symatrix students in East Basaman in Arabic, both linguistically and non-linguistically. The teacher is interested in the student's pronunciation on the differences in phonemic functions that lead to errors in changing the meaning of words, the words are pronounced correctly. That the teacher uses secondary pair exercises, such as: walking and being, and paying attention to the students' pronunciation. The teacher explains with direct explanation how to distinguish letters and their descriptions with the help of signs and movements of the face and hand. The teacher encourages the students to overcome their mistakes and explains to the students the importance of the Arabic language for them.